Effects of structural damping on wind-induced responses of a 243-meter-high solar tower based on a novel elastic test model. Issue 172 (January 2018) - Li, S.Y.; Liu, M.; Li, H.X.; Hui, Y.; Chen, Z.Q.
Abstract: The effects of structural damping to the responses of the vortex-induced vibration of solar tower should be investigated carefully to provide a reference for the structural designers. A new type of elastic test model for a 243-meter-high solar tower is particularly designed and manufactured. A core beam is designed in the test model to simulate the stiffness of the concrete structure, and a coat with baseplate (like a cup) is designed to simulate the steel structure. A structural damping ratio as low as 0.3% is realized, and four level of structural damping ratio, including 0.7%, 1.0%, 1.5% and 2.0%, can be conveniently achieved. A series wind tunnel tests are carried out to investigate the features of the wind-induced responses of the solar tower at the structural damping level of 0.3%, 0.7%, 1.0%, 1.5% and 2.0%. The results show that obvious vortex-induced vibration could be found within wind velocity range of U 10 = 21.5–28.4 m/s for the structural damping ratio of 0.7%. At this time, the highest vortex-induced responses (at the wind velocity of U 10 = 23.2 m/s), including acceleration at the top, base shear and base moment, are far larger than those at the design wind velocity ( U 10 = 41.0 m/s). Moreover, it appears that the wind-induced responses in cross-wind direction are far higher than those in the along-wind direction. The most important point is that the base shear and moment in the cross-wind direction measured from wind tunnel tests are far higher than the values obtained from the Code ACI 307–08. The wind-induced responses of the solar tower are extremely sensitive to the structural damping of the test model. For example, the highest acceleration, base shear and moment in cross-wind direction are respectively reduced by about 67%, 74%, 71% when structural damping ratio slightly increases from 0.7% to 1.0%. It seems that the vortex-induced vibration of the solar tower could be effectively mitigated if the structural damping ratio could be enhanced over 1.0%. Highlights: A novel elastic model for solar tower is designed and manufactured to realize a very small structural damping ratio. The structural damping of the test model could be conveniently adjusted. The effects of structural damping to wind-induced responses of the solar tower are studied based on wind tunnel tests.